Mainstreaming sustainable innovation: unlocking the potential of nature-based solutions for climate change and biodiversity. Issue 132 (June 2022) - Xie, Linjun; Bulkeley, Harriet; Tozer, Laura
Abstract: Sustainable innovation has been widely acknowledged as the key driver for societal transitions towards sustainability. Recently, there have been widespread calls to mainstream nature-based solutions (NBS), a form of socio-ecological-technical innovation, to address urban sustainable development concerns especially for climate change and increasingly for biodiversity loss. However, what mainstreaming means and how sustainability-oriented innovations like NBS can be mainstreamed to benefit multiple agendas remains underexplored. In this paper, we first critically discuss existing literature on mainstreaming and argue that the common understanding of the concept rooted in policy sciences does not fit the governance context in which urban innovations like NBS are being shaped and adopted. Drawing on sustainability transitions and urban studies literature, we then propose a new approach that promotes the use of NBS to deliver multiple sustainability goals simultaneously. We argue that mainstreaming NBS relies on identifying and acting on a certain set of key forms of interventions - stepping stones - that can facilitate the embeddedness and maintenance of NBS across urban infrastructure regimes. Based on case studies of existing European practices, we identify pivotal stepping stones and promising pathways for mainstreaming NBS for climate change and biodiversity separately and explore what this means for addressing both agendas simultaneously. Highlights: Mainstreaming innovations involves both normalization and the retention of novelty. Stepping stones are generic forms of viable interventions proven in practice. Pathways for mainstreaming can be created by assembling stepping stones. Key stepping stones vary depending on goals of nature-based solutions (NBS). Acting on shared stepping stones can mainstream NBS for multiple goals.